A design studio experience: impacts of social sustainability. (15th July 2019) - Ceylan, Salih; Soygeniş, Murat Deniz
Abstract : Purpose: Sustainability, especially in terms of development and growth, has been in the agenda of the world community for several decades. However, apparently not all the aspects of sustainability are given equal importance. Ecologic and economic components of sustainability have been in the focal point of many theoretical and practical works, as the social aspect has been mostly left out of emphasis. The purpose of this paper is to examine the social aspects of sustainability and its relation to architecture, with respect to the strong connection between the society and the built environment. Design/methodology/approach: The core of the paper consists of a case study conducted at a design studio course for third-year architecture students whereas the outcomes of the student works on the design problem are evaluated as examples for design approaches to reflect the effects of the built environment on social sustainability. The case study is supported with a literature review and examination of existing approaches to similar subjects regarding social sustainability. Findings: The findings resulted in a better understanding of social sustainability in architectural education which is reflected on the built environment through several architectural strategies. Originality/value: This paper contributes to the literature by providing a holistic understanding of sustainability including its social aspects and creating an awareness for the importance of social sustainability in architectural education.